2020
DOI: 10.3390/metabo10090360
|View full text |Cite
|
Sign up to set email alerts
|

An 1H NMR- and MS-Based Study of Metabolites Profiling of Garden Snail Helix aspersa Mucus

Abstract: Metabolic profiling based on 1H nuclear magnetic resonance (NMR) spectroscopy was applied with the aim to investigate the functional role of the metabolites in lyophilized mucus from the garden snail Helix aspersa. Twenty metabolites were unambiguously identified by 1H, 1D TOCSY, 2D J-resolved, 2D COSY, and 2D HSQC NMR spectra with water suppression. The metabolic profiles of two fractions with low molecular weight (Mw < 1 kDa and Mw < 3 kDa) are very similar. Metabolites with known antioxidant, antibact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…It is worth noting that observed results agree with the literature. In detail, H. aspersa mucus is a well‐known source of different amino acids, like proline and glycine found in different snail species, and sulfur‐bearing peptides 50 . Among these, glutathione (GSH) derivatives deserve a special attention, because their sulfhydryl group (−SH) belonging to cysteine units is involved in reduction and conjugation reactions for the removal of peroxides and many xenobiotic compounds, making them the major endogenous intracellular antioxidants 51 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that observed results agree with the literature. In detail, H. aspersa mucus is a well‐known source of different amino acids, like proline and glycine found in different snail species, and sulfur‐bearing peptides 50 . Among these, glutathione (GSH) derivatives deserve a special attention, because their sulfhydryl group (−SH) belonging to cysteine units is involved in reduction and conjugation reactions for the removal of peroxides and many xenobiotic compounds, making them the major endogenous intracellular antioxidants 51 .…”
Section: Resultsmentioning
confidence: 99%
“…In detail, H. aspersa mucus is a well-known source of different amino acids, like proline and glycine found in different snail species, and sulfur-bearing peptides. 50 Among these, glutathione (GSH) derivatives deserve a special attention, because their sulfhydryl group (−SH) belonging to cysteine units is involved in reduction and conjugation reactions for the removal of peroxides and many xenobiotic compounds, making F I G U R E 1 MALDI (+) FT-ICR mass spectrum (A) and Van Krevelen diagram (B) obtained by the analysis of a sample of pure snail slime (SS). In plot B, types of formulae are distinguished by colors, that is, blue for CHO, green for CHON, red for CHONS, purple for CHOS, and yellow for CHN type them the major endogenous intracellular antioxidants.…”
Section: Maldi (+) Ft-icr Ms Analysismentioning
confidence: 99%
“…Our previous studies described the antimicrobial activities of different fractions from the mucus of the garden snail C. aspersum, and characterized metabolites and antimicrobial peptides [34][35][36][37]. This study upgraded the previous data and provided additional information on new peptides and protein fractions with antibacterial activity in the mucus of C. aspersum.…”
Section: Introductionmentioning
confidence: 83%
“…Bioactive compounds, such as proteins, peptides, and glycopeptides, are present in the mucus of many mollusks (Pitt et al, 2015). Recently, many compounds with antimicrobial and antioxidant activity, as well as regenerative properties were detected in the snail mucus (Dolashki et al, 2020; Pitt et al, 2019; Vassilev et al, 2020). Dolashki et al (2020) found that different peptide and protein fractions from the mucus of garden snail C. aspersum , manifest antibacterial activity against Gram negative ( Pseudomonas aureofaciens and Escherichia coli ) and Gram positive ( Brevibacillus laterosporus ) bacterial strains as well the anaerobic bacterium Clostridium perfringens (Dolashki et al, 2020).…”
Section: Discussionmentioning
confidence: 99%